POTENSI DILLA HIKMAH SARI DALAM MEMENANGKAN PILKADA SERENTAK KABUPATEN TANJUNG JABUNG TIMUR 2024 - Rahmatullah, Ahmad Fajar (Jurnal Politik Pemerintahan Dharma Praja, 2022)
This article aims to analyze Dilla Hikmah Sari's potential victory in the 2024 regional elections. The writing of this article uses a descriptive qualitative method with data collection techniques using library research, namely data collection techniques using various literatures such as books, magazines, journals, and previous research reports. The results showed that Dilla Hikmah Sari's modalities when viewed from social capital and political capital at least illustrate that there is little chance of winning the 2024 regional elections. dependence on the influence of his father who was a former regent for 2 terms. The only hope that Dilla Hikmah Sari has is the legitimacy that will later be given by Romi Haryanto as an incumbent in providing support to Dilla Hikmah Sari if we look at it from a "spoil system" perspective because it has helped win her in the 2020 simultaneous elections. Romi Haryanto has a network and so far his network loyalty has been quite tested as we saw in the last December 2020 regional election which won 76.8%. Therefore, Dilla Hikmah's lack of political modality at least makes Dilla consider it a political safari to political party elites in East Tanjung Jabung Regency, at least get a political vehicle to be able to advance in the 2024 simultaneous regional elections by considering the opportunities that exist..